Factors influencing on functional independence outcomes after hospitalization and rehabilitation in children with spinal cord injury - Hong-Bo Zhao; Xiang-Jiang Rong; Qi Zhang; Ting-Ting Ma; He Yan; Tian-Tian Zhou; Yan-Qing Zhang (BMC Pediatrics)
Abstract Objective This study is to investigate the factors that influence functional autonomy outcomes in children who have undergone rehabilitation for spinal cord injury. The aim is to enhance the clinical guidance provided to inpatients at the China Rehabilitation Research Center, Beijing Bo-ai Hospital. Furthermore, the objective is to optimize rehabilitation interventions and establish a scientific basis. Methods This study employed a retrospective survey method for data collection and analysis. Descriptive analysis, one-way ANOVA analysis, and Multiple logistic regression analysis were utilized to examine the influencing factors associated with the prognosis of functional independence outcomes in children with SCI. The degree of influence of each independent variable on functional independence outcomes was ultimately determined. Results The total score of SCIM-III at admission was 41.48 ± 4.089, and the total score of SCIM-III at discharge was 50.05 ± 25.028, resulting in a significant difference in the total score of SCIM-III was (8.57 ± 7.000, p < 0.001).In one-way ANOVA analysis, Self-care: injury segments, damage plane, ASIA, assistive devices, complications, rehabilitation duration treatment, WISCI-II, UEMS and LEMS, BI, and 6WMD groups were statistically significant (p < 0.001). Respiratory and sphincter management: injury segments, ASIA, complications, injury to recovery time interval, rehabilitation duration treatment, WISCI-II, UEMS and LEMS, BI, and 6WMD groups were statistically significant (p < 0.05). Move: age, injury segments, damage plane, rehabilitation duration treatment, WISCI-II, UEMS and LEMS groups were statistically significant (p < 0.05). SCIM-III total score: age, AISA, assistive devices, injury to recovery time interval, rehabilitation duration treatment were statistically significant (p < 0.05). Multiple logistic regression analysis, revealed that the injury to recovery time interval had a negative correlation with the total difference in SCIM-III scale (t = −9.893, p < 0.001; 95%CI-12.006~-7.780), while the duration of rehabilitation treatment (t = 4.245, p < 0.001, 95%CI 2.636 ~ 5.854) had a positive correlation with different age groups (t = 4.002, p < 0.001, 95%CI 2.421 ~ 5.583). Conclusion The shorter the interval between the time of spinal cord injury and the time of intervention for rehabilitation, the more favorable the functional recovery of the children. Children with SCI who were hospitalized for rehabilitation and achieved 3-month daily functional independence scores were more successful. It is recommended that rehabilitation interventions for children with SCI in this institution should be initiated as early as possible and maintained over time. Among the subjects, the prognosis of functional independence was more favorable in the school-age group (6-18y) than in the preschool group (3–6 y).